2009
DOI: 10.5539/ijbm.v3n4p157
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis on Bankers’Perceptions on Islamic Banking

Abstract: This research was conducted to gauge the perceptions of employees, in both Islamic banks and conventional banks, of Islamic products and services, the training and experience gained in Islamic banking, and the potential of Islamic banking in Malaysia. Questionnaires dealing with Islamic banking were distributed to bankers in the northern part of Malaysia. The results revealed that bankers in Islamic banks have more positive perceptions on the above issues. Interestingly, few of the bankers possessed a relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 11 publications
6
53
1
1
Order By: Relevance
“…However, further analysis found that only underlying principle and training are having significant influence to the product knowledge of employees. The finding corresponds to the study by Zainol et al (2008) and Aslam et al (2011), who also found that training is one of the important factors that the management used to evaluate the knowledge of their banking staff. By having insufficient trainingand working experience, the Islamic banking employees cannot provide accurate knowledge of the products and persuade the customers to use the Islamic banking products.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…However, further analysis found that only underlying principle and training are having significant influence to the product knowledge of employees. The finding corresponds to the study by Zainol et al (2008) and Aslam et al (2011), who also found that training is one of the important factors that the management used to evaluate the knowledge of their banking staff. By having insufficient trainingand working experience, the Islamic banking employees cannot provide accurate knowledge of the products and persuade the customers to use the Islamic banking products.…”
Section: Discussionsupporting
confidence: 57%
“…In general perception is the ability to understand the differences and often identified by the level of satisfaction on certain products or services. Previous studies found that there was a positive perception of training and experience on Islamic banking among bankers in Malaysia (Zainol et al, 2008). Likewise it is found in Pakistan by Aslamet al (2011) that bankers in the Islamic banks have more positive perception on issues compared to bankers of conventional banks.…”
Section: Product Knowledge and Perceptionmentioning
confidence: 80%
See 3 more Smart Citations